On Some Complete Tripartite Graphs that Decline Continuous Monotonic Decomposition - Varghese, Joseph; Antonysamy, A. (Asian Journal of Engineering and Applied Technology, 2012)
A collection of complete tripartite graphs, viz., K1,3,m, K2,3m, K2,5m and K3,5,m do not accept Continuous Monotonic Decomposition(CMD). It is shown that by an addition or removal of a single edge will make these graphs accept CMD. Eventually, the discussion helps to find a series of numbers which are not triangular.